Insights on Urban Tomorrows – Expert Survey on Futures of Liveable Cities - Marjukka Parkkinen; Sirkka Heinonen (Finland Futures Research Centre, University of Turku, 2022)
This paper presents the results of an international survey on futures of liveable cities conducted by Finland Futures Research Centre (FFRC), University of Turku, and the Helsinki Node of the Millennium Project. Seven experts combining both futures studies and urban studies were invited to answer a questionnaire. The aim of the survey was to feed insights to the foresight part of the ENCORE (2015–2016) research project. As the opinions on what is a liveable environment differed by contents, so did the insights on how a liveable city can be enabled. The responses are presented in this working paper with some related analysis by the project team at FFRC. The emphasis in creating liveable cities seems to lie on cultural, social, and environmental factors, technology featuring as an enabler. The changing social and power relations within the cities is also emerging as an interesting topic, calling for further interdisciplinary foresight study.